Parental socioeconomic and educational level and child overweight – lessons from a municipality based study - Silva, Ana Lúcia (2012)
Childhood obesity is one of the most serious Public Health problems in Portugal. Unhealthy food habits and physical activity low levels seems to be the major factors behind this epidemic (1,2,3). According to the literature the socioeconomic conditions can contribute as an obesogenic factor, particularly in families with low incomes and medium educational levels (4). In order to control and reverse the Portuguese trends, community-based programs seems to respond effectively to the childhood obesity condition and their multifactor's (5,6).